Pelatihan Pengelolaan Badan Usaha Milik Desa untuk Meningkatkan Kompetensi Manajerial dan Tata Kelola Organisasi - I Made Madiarsa; Putu Sukma Kurniawan (Ilin Institute, 2023)
This community service project aims to enhance the managerial proficiency and organizational governance of BUM Desa Vally Karya Lestasi's management in Bengkala, Buleleng. The implementation method comprises of three phases, namely initial observation, core stage, and monitoring stage. The core stage involved providing socialization and training to the BUM Desa management. The provided information concerns the management of BUM Desa in accordance with applicable regulations and strategies for achieving good organizational governance. The outcomes demonstrate that the management has a solid grasp of managerial competency and organizational governance. It is anticipated that the findings will assist the BUM Desa management in effectively managing the organization.